For example, the national identity of the Kurdistan Region in the transitional society of Kurdistan - Saadi, Asst.L. Khadija Rahman; Mahmoud, L. Burhan Omar (Sulaimani Journal for Humanities, 2025)
Identity is directly related to people’s understanding of “who” they are, “what they are” and what matters to them. This understanding is linked to a number of characteristics that make one person different from another, one nation from another. The concept of national identity is a relatively new phenomenon in political and social science, which dates back to the formation of the nation-state in Until this historical event, political identities were usually defined within the framework of tribes, regions, groups, and religions, and at a more general level, under the names of empires and nations. Some studies of Kurdology indicate that Kurdish society is in a transitional period. For any sociological researcher, if he looks closely at the structure, movement and current social situation of Kurdish society, he will see some of the signs of this transition. For example, after the 1991 uprising, the Kurdistan Region entered a transitional phase in two situations. The first is the de facto-order situation, which lasted from 1991 to the second situation is the constitutional situation, which has been in place since 2003 within the Iraqi state. That is why this study focuses on this important issue, national identity in a transitional society. The issue of nation and identity is a sensitive and important issue in the Middle East, especially in transitional and decolonized societies. In this paper, we will focus on theories on the issue of colonized nations, such as Kurdish society. Therefore, through sociological and political theory, we want to talk about stateless nations. There are many different ways and mechanisms for these nations to internationalize their national issues, especially now that we are in the era of technology and artificial intelligence. For this purpose, the study will be conducted using comparative and historical methods. This study also seeks to answer the questions: What is identity? What is the stage of Kurdish nationalism? Is the previously legitimate identity in crisis?
Keywords: nation; national identity; nationalism; transitional society; stateless nation